Prenatal exposure to extreme ambient heat may amplify the adverse impact of Superstorm Sandy on basal ganglia volume among school-aged children - Donato DeIngeniis; Melissa Blum; Rebecca M. Lee; Ahmed Duke Shereen; Yoko Nomura (PLoS ONE, 2025)
Background Weather-related stressors on healthy brain development has become an important topic in recent years. Notably, prenatal stress exposure to natural disasters may disrupt child neurodevelopment, with recent research exploring its impact on child brain morphology. Prenatal exposure to extreme weather events, such as ambient heat, may also affect child brain morphology. The basal ganglia, while historically related to motor ability, has gained increasing attention for its role in various non-motor functions, such as emotion regulation. Leveraging an existing cohort with and without prenatal exposure to Superstorm Sandy (SS), a category 3 hurricane at its peak, this study aims to investigate how prenatal exposure to both a natural disaster and extreme ambient heat impacts this important subcortical region. Methods Main effects of SS and extreme heat exposure on basal ganglia volume were first analyzed to examine the independent effect on brain outcomes. Moderation models subsequently explored the potential role extreme heat had on the association between SS and basal ganglia volume. We used magnetic resonance imaging to measure basal ganglia gray matter volume at age 8 among 11 SS-exposed and 23 non-exposed children. Results The SS-exposed group, relative to their non-exposed counterparts, had significantly larger volume in the putamen and pallidum bilaterally, and right caudate. No notable main effects of extreme heat were found. Moderation models revealed, however, extreme heat exposure amplified the adverse impact of SS exposure on basal ganglia volume, evidenced by reduced left nucleus accumbens and increased left pallidum volume. Conclusions Prenatal exposure to SS impacted child brain development. Extreme heat amplified this risk via increased and reduced brain volume from different basal ganglia subregions. Alongside promoting initiatives to combat climate change, increasing awareness of the potential dangers of exposure to extreme climate events for pregnant individuals is vital for protecting long-term child brain development.